Surface Engineered Polymeric Biomaterials with Improved Biocontact Properties - Todorka G. Vladkova (International Journal of Polymer Science)
We present many examples of surface engineered polymeric biomaterials with nanosize modified layers, controlled protein adsorption, and cellular interactions potentially applicable for tissue and/or blood contacting devices, scaffolds for cell culture and tissue engineering, biosensors, biological microchips as well as approaches to their preparation.